COMIC DEVELOPMENT BASED ON DISCOVERY LEARNING AS THE LITERATION INCREASING MEDIA FOR ELEMENTARY STUDENTS - Yohana Intan Dili Susanti; Wahyudi Wahyudi; Yohana Setiawan (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract : Comic Development Based On Discovery Learning As The Literation Increasing Media For Elementary Students. The purpose of this study is to develop and test the validity, practicality, and effectiveness of comic media with the basis of discovery learning on thematic learning in elementary schools. The  research method used was R&D and the ADDIE design which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The validity of the product was tested by experts by using media, material, and learning expert validation instruments. The practicality of the product was seen from the questionnaire of student responses to the media. Product effectiveness was seen from the results of the assessment of the three aspects of literacy, namely the process of understanding, the purpose of reading, and the attitude of reading from a reading and comic. This research produces comic based discovery learning as a medium to improve the literacy of elementary school students. This comic proved to be valid, as seen from the expert media and material test. Comics proved to be practical, seen from student responses to media questionnaires. Comics proved to effectiveness, seen from the result of the assessment of the three aspects of literacy. Keywords: Comic based on Discovery Learning; Media; Literacy  Abstrak : Pengembangan Komik Berbasis Discovery Learning Sebagai Media Meningkatkan Literasi Siswa Sekolah Dasar. Tujuan dari penelitian ini adalah untuk mengembangkan dan menguji kevalidan, kepraktisan, dan keefektifan dari media komik berbasis dicovery learning pada pembelajaran tematik di Sekolah Dasar. Metode penelitian ini adalah R&D dan menggunakan desain ADDIE yang memiliki 5 tahap yaitu Analysis, Design, Development, Implementation, dan Evaluation. Kevalidan produk di uji oleh pakar dengan menggunakan instrumen validasi pakar media, materi, dam pembelajaran. Kepraktisan produk dilihat dari angket respon siswa terhadap media. Keefektifan produk dilihat dari hasil penilaian dari ketiga aspek literasi yaitu proses pemahaman, tujuan membaca, dan sikap membaca dari sebuah bacaan dan komik. Penelitian ini menghasilkan komik berbasis discovery learning sebagai media untuk meningkatkan literasi siswa Sekolah Dasar. Komik ini terbukti valid, dilihat dari uji pakar media dan materi. Komik terbukti praktis, dilihat dari angket respon siswa terhadap media. Komik terbukti efektif, dilihat dari hasil penilaian ketiga aspek literasi. Kata kunci : Komik Berbasis Discovery Learning; Media; Literasi